Biopolityczne horyzonty — między biopolityką tradycyjną a biopolityką nowoczesną - Gregorczuk, Karol (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The subject of the article is an analysis of the general concept of biopolitics in contemporary discourse and the issues of crossing two aspects of two types of biopolitics: traditional biopolitics and modern biopolitics, as well as their function in a broader understanding of economic activity. Generally speaking, biopolitics means the form of management by power centers of control of bio-logical processes, which establish normative levels of life and death. A literature review shows broad theoretical considerations (e.g. M. Foucault, G. Agamben). In this reflection on biopolitics, I would like to take into account the multidimensional optics, covering global economic, cultural, and political processes, with a special emphasis on the normative level of these processes. The theoretical analysis will focus on the issues of crossing two given types of biopolitics: traditional biopolitics and modern biopolitics, as well as trying to find changes in their broadly understood social activities.
Keywords: modern biopolitics; traditional biopolitics; life; body; Foucault, Michael (1926-1984); Agamben, Giorgo (1942-)